2021
DOI: 10.3390/s21072335
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Update of the Latest Evidence for CardioMEMS Pulmonary Artery Pressure Monitoring in Patients with Chronic Heart Failure: A Promising System for Remote Heart Failure Care

Abstract: The CardioMEMS pulmonary artery (PA) monitoring system placed in the left lower lobe pulmonary artery is capable of measuring pulmonary artery pressure remotely as a surrogate of intracardiac filling pressures and volume status. The technique is safe and reliable. By using remote PA monitoring for proactive medical interventions, there is a growing body of clinical evidence for a substantial, robust reduction in HF hospitalizations in various populations (clinical trial setting, post-marketing studies and real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The CardioMEMS™ (CardioMEMS HF System, Abbott, Sylmar, CA) is an implantable wireless sensor placed in the left lower lobe pulmonary artery (through a catheter-delivery system), capable of remotely measuring PAP [18]. It is the only invasive HF remote monitoring sensor with Food and Drug Administration (FDA) approval and European Conformity (CE) mark [19]. Patients take daily home measurements with an external electronics system and transmit the PAP data wirelessly for clinician review [18,19].…”
Section: Cardiomems™ Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…The CardioMEMS™ (CardioMEMS HF System, Abbott, Sylmar, CA) is an implantable wireless sensor placed in the left lower lobe pulmonary artery (through a catheter-delivery system), capable of remotely measuring PAP [18]. It is the only invasive HF remote monitoring sensor with Food and Drug Administration (FDA) approval and European Conformity (CE) mark [19]. Patients take daily home measurements with an external electronics system and transmit the PAP data wirelessly for clinician review [18,19].…”
Section: Cardiomems™ Technologymentioning
confidence: 99%
“…It is the only invasive HF remote monitoring sensor with Food and Drug Administration (FDA) approval and European Conformity (CE) mark [19]. Patients take daily home measurements with an external electronics system and transmit the PAP data wirelessly for clinician review [18,19]. The recent studies showed that the CardioMEMS™ reduced HF hospitalizations and improved quality of life (Table 2) [46][47][48][49][50][51].…”
Section: Cardiomems™ Technologymentioning
confidence: 99%
See 1 more Smart Citation
“… 65 Classic methods for ambulatory HF monitoring such as daily weights and symptom monitoring have failed to mitigate HF hospitalizations. 66 Simultaneously, there is an increased appreciation of the fact that changes in intracardiac pressures precede signs of overt congestion and can therefore provide early knowledge about incident decompensation. 42 This has led to increased enthusiasm around the use of remote invasive monitoring tools, namely the CardioMEMS HF system with multiple clinical studies demonstrating safety and clinical efficacy.…”
Section: Moving Targets Of the Futurementioning
confidence: 99%
“…This leads to patient noncompliance, which is thought to be a major driver of hospital readmissions 8–10. Clinically, other solutions such as apps reminding patients to take measurements,11 voice-response systems12 for daily measurements, or implantable devices such as CardioMems13 or Heartlogic14 have been used. However, these methods all suffer from reliability issues,15 have poor patient compliance, have significant drop-off rates16 after their installation/setup and/or are very costly 17…”
Section: Introductionmentioning
confidence: 99%